Protective effects of minocycline on experimental spinal cord injury in rats. Issue 8 (August 2015) - Aras, Mustafa; Altas, Murat; Motor, Sedat; Dokuyucu, Recep; Yilmaz, Atilla; Ozgiray, Erkin; Seraslan, Yurdal; Yilmaz, Nebi
Abstract Background The effects of minocycline on neuronal injury after spinal cord injury (SCI) are limited and controversial. Therefore we aimed to investigate the protective effects of minocycline on tissue and on serum concentrations of malondialdehyde (MDA) levels, superoxide dismutase (SOD) activity, glutathione peroxidase (GSH-Px) activity, tissue total antioxidant and oxidant status (TAS and TOS, respectively), and AST and LDH levels in rats with SCI. Methods This study was performed on 7–8 weeks 38 male Wistar albino rats. The animals were randomly divided into five groups: group 1, Sham (n = 8); group 2, SCI (spinal cord injury)/control (n = 8); group 3, SCI + minocycline3 (n = 7); group 4, SCI + minocycline30 (n = 8) and group 5 SCI + minocycline90 (n = 7). Blood and tissue samples were analysed for MDA, SOD, GSH-Px, TAS, TOS, AST and LDH levels. Results The MDA levels were significantly higher in SCI group compared to sham group (p < 0.001), and MDA levels were also significantly higher in SCI group compared to SCI + M3, SCI + M30, SCI + M90 (p < 0.05). SOD levels were significantly higher in SCI + M30 when compared to SCI and SCI + M3 groups (p < 0.05). GSH-Px levels decreased significantly in SCI and SCI + M3 groups compared to sham (p < 0.05). SCI + M3 group showed significantly decreased levels of TAS and TOS compared to SCI group (p < 0.05). TAS and TOS levels significantly increased in SCI + M90 group compared to SCI + M3 and SCI + M30 groups (p < 0.05). Conclusions The present study demonstrates the dose-dependent antioxidant activity of minocycline against spinal cord injury in rats. Minocycline administration increased antioxidant enzyme levels and improved total antioxidant status.